Secreted and transmembrane Wnt inhibitors and activators - Sirrenberg-Cruciat, Cristina-Maria; Niehrs, Christof (Cold Spring Harbor perspectives in biology, 2013)
Signaling by the Wnt family of secreted glycoproteins plays important roles in embryonic development and adult homeostasis. Wnt signaling is modulated by a number of evolutionarily conserved inhibitors and activators. Wnt inhibitors belong to small protein families, including sFRP, Dkk, WIF, Wise/SOST, Cerberus, IGFBP, Shisa, Waif1, APCDD1, and Tiki1. Their common feature is to antagonize Wnt signaling by preventing ligand-receptor interactions or Wnt receptor maturation. Conversely, the Wnt activators, R-spondin and Norrin, promote Wnt signaling by binding to Wnt receptors or releasing a Wnt-inhibitory step. With few exceptions, these antagonists and agonists are not pure Wnt modulators, but also affect additional signaling pathways, such as TGF-β and FGF signaling. Here we discuss their interactions with Wnt ligands and Wnt receptors, their role in developmental processes, as well as their implication in disease., Ten families of Wnt antagonists (including the Dkk family) and two families of agonists (R-spondin and Norrin) are known to date. Most are not pure Wnt modulators; they affect other pathways as well.
Gesehen am 28.05.2021